The economic efficiency of apple production in terms of post‑harvest technology - Szabó , Viktor (Applied Studies in Agribusiness and Commerce, 2014)
This study analyses how the level of postharvest technology’s development influences the economic efficiency of apple production with the help of a deterministic simulation model based on primary data gathering in producer undertakings. To accomplish our objectives and to support our hypotheses three processing plant types are included in the model: firstly apple production with no postharvest and prompt sale after the harvest, secondly parallel production and storage combined with an extended selling period and thirdly production and entire postharvest infrastructure (storage, sorting-ranking, packing) with the highest level of goods production and continuous sales. Based on our results it can be stated that the parallel production (plantation) and cold storage, so the second case is proved to be totally inefficient, considering that the establishment of a cold storage carries enormously high costs with resulting a relative low plus profit compared to the first type of processing plant. The reason for this is that this type is selling bulk goods without sorting-grading or packaging; storage itself – as a means of continuously servicing the market – is not covered properly by the consumers. Absolute efficiency ranking cannot be established regarding the other two processing plants: plantation without post-harvest infrastructure resulting lower NPV, but a more favourable IRR, DPP and PI as developing a plantation and a whole post-harvest infrastructure.